Development of Surface‐Engineered Tape‐Casting Method for Fabricating Freestanding Carbon Nanotube Sheets Containing Fe2O3 Nanoparticles for Flexible Batteries. Issue 6 (26th February 2018) - Karam, Zainab; Susantyoko, Rahmat Agung; Alhammadi, Ayoob; Mustafa, Ibrahim; Wu, Chieh‐Han; Almheiri, Saif
Abstract : Chemical vapor deposition and filtration are commonly used to fabricate freestanding multiwalled carbon nanotube sheets containing iron(III) oxide (Fe2 O3 ) (MWCNT–Fe2 O3 sheets). However, the former is relatively expensive, and the latter suffers from poor scalability. Here, the authors develop an inexpensive, scalable, high‐throughput, tunable tape‐casting method for fabricating flexible, foldable freestanding MWCNT–Fe2 O3 sheets. When tested as electrodes in lithium‐ion batteries, the sheets perform better than conventional graphite on copper foil (681 mAh g −1 after 20 cycles at 100.5 mA g −1 /0.1 C‐rate vs. 72.5 mAh g −1 after 20 cycles at 37.2 mA g −1 /0.1 C‐rate). Sheets prepared at Fe2 O3 :MWCNT mass ratios ranging from 1/4 to 2/1 are flexible and easy to be separated from the substrate, but a sheet prepared at a 9/1 ratio is not. The ratio can be tuned to suit various applications. Sheets with high (low) Fe2 O3 :MWCNT mass ratios has high (low) charge‐transfer resistance and are suitable for applications requiring high energy density (high power density). Mechanical compression of the sheets flattens them and increase their density from 0.449 to 0.771 g cm −3, which in turn increases their electrical conductivity from 3.56 × 10 3 to 5.73 × 10 3 S m −1 . Abstract : The authors fabricate freestanding MWCNT‐Fe2 O3 sheets for flexible batteries via surface‐engineered tape‐cast. The lithium storage of MWCNT‐Fe2 O3 sheets is tested with different Fe2 O3 /MWCNT mass ratio. MWCNT‐Fe2 O3 sheets show better performance than conventional graphite on copper. Physical and electrochemical characterizations are performed.